FEATURES OF FORMATION OF FUNCTIONAL COVERINGS AT ELECTROSPARK MODIFYING OF METAL MATERIALS - D. N. Korotaev; E. V. Ivanova (Вестник СибАДИ, 2017)
Results of a research of influence of materials of the alloying electrodes at electrospark modifying of steel products on phase structure of the formed coverings and blankets are presented. It is established that when processing the electrode on the basis of carbide of the titan with additives of nickel, chrome, aluminum and a sheelitovy concentrate, in a covering forms the strengthening phase ‒ intermetallic compound Ni3(AlTi). Possible mechanisms of hardening of blankets of metal products at electrospark modifying are considered, and also results of a research of influence of the gas interelectrode environment on covering thickness, density of defects of a crystal structure of materials and tribological properties of the modified blankets and coverings. Use of technology of electrospark processing promotes manifestation of a complex of mechanisms of hardening from which dominating are dispersive hardening coherent particles of carbides and intermetallic compound, and also a strongly solution alloying. The received results demonstrate active participation of the gas environment in change of physicomechanical and tribological properties of coverings and blankets. So, at electrospark processing in the atmosphere of oxygen the minimum thickness of a covering (about 30 μm) and the maximum wear resistance is recorded. It is connected with the fact that crystalline state of the surfaces received in the oxygen-containing environment is characterized by the increased density of dislocations. Besides, according to the X-ray phase analysis, under a microdimensional covering the disperse strengthened blanket with formation of intermetallic compound settles down that also promotes increase in extent of hardening of a steel surface. It is shown that the reasonable choice of a ratio of the mechanisms of hardening operating when processing with electrospark modifying allows to provide a necessary complex of physicomechanical and tribological properties of the formed coverings.